Special education and minority ethnic young people in England: continuing issues. Issue 4 (3rd July 2016) - Tomlinson, Sally
ABSTRACT: In countries that have developed special education (SE) provision, whether in segregated settings or 'included' in mainstream, racial, ethnic and immigrant minorities continue to be disproportionately represented. Explanations for placement in SE programmes continue to centre round assumptions of deficiencies in student abilities to learn and 'behave', their family backgrounds and communities. Many policy-makers, politicians, schools and teachers ignore or are ignorant of the historical background and social contexts in which these students are expected to learn. The article overviews some of this history and policy responses concerned with SE, low attainment and troublesome school behaviour in England, including recent evidence and current explanations for the placement of the students. A premise here is that research, policy and literature are still separating what is happening in 'special' education from other areas of education. This cannot continue, as world-wide moves towards inclusive education have meant that mainstream schools and colleges now incorporate (or still exclude) a range of students regarded as having learning difficulties or disabilities, and all young people are now expected to acquire some kind of qualification or be prepared for independent living.